Resistance to fractures of endodontically treated teeth restored with fiberglass post and cores using CAD / CAM: literature review - I. A. Voronov; O. S. Mordanov; I. M. Todua; Sh. A. Nazhmudinov (LLC "Endo Press", 2020)
Individual manufacturing of post and core systems using CAD-CAM technology allows to quickly and efficiently adapt these structures in the root canal. Today, there are a number of materials, one of which is fiberglass, that is intended for milling. The aim of this literature review is to assess fracture resistance of endodontically treated and reconstructed using fiberglass post and cores using CAD / CAM based on available publications.